DESIGNING E-KING (English speaKING) MASTERY AS LEARNING MEDIA FOR X GRADE STUDENTS - Dina Rizkia Fitrillah; Iin Baroroh Ma arif; Luluk Choirun Nisak Nur (Bajang Institute, 2021)
The background for the development of E-KING (English speaKING) Mastery media is to see the condition of learning media in general. In senior high school or Madrasah Aliyah Sayyid Abdurrahman learning still uses the usual method without media. Learning media is needed to facilitate teachers in transferring knowledge and making it easier for students to understand English material. Therefore, the purpose of this study is to develop E-KING (English speaKING) Mastery learning media to X grade students at Senior High School. The research method used is Research and Development, this development used ADDIE learning model which consists of five steps, that : 1) Analyze, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The results of this assessment indicate that the E-KING (English speaKING) Mastery media has “very good” feasibility, according to media expert getting an average of 4,07 and material expert 4,13. Subject of this research was students of X Grade students at Madrasah Aliyah Sayyid Abdurrahman Pagerwojo Perak Jombang. The students responses of try out result 81,41 which means this Learning Media is